Meninjau Kemandirian Anak Usia Dini melalui Gaya Pengasuhan Demokratis di PAUD As-Sa’adah Kota Cilegon - Haeriyah, Haeriyah; Laili, Mahsiani Mina; Mulyawan, Galuh (Darul Yasin Al Sys, 2024)
This study aims to examine the influence of democratic parenting styles on the independence of early childhood in schools, highlighting the factors that support the development of such independence. The background of this research stems from the importance of independence in early childhood as a foundation for future academic and social success. Democratic parenting, characterized by open communication, children's participation in decision-making, and respect for their needs and feelings, is hypothesized to play a significant role in fostering children's independence. Using a qualitative method with in-depth interviews, the research findings indicate that children raised with democratic parenting are more capable of making their own decisions, showing initiative, and having higher responsibility in school. The discussion of this study emphasizes that in addition to parenting style, factors such as a supportive school environment, active teacher involvement, and collaboration between parents and the school also play an important role in shaping children's independence. The conclusion of this study affirms that the implementation of democratic parenting and a supportive school environment is crucial in developing early childhood independence. Recommendations are given to parents and teachers to strengthen communication and collaboration in supporting children's independence in school, to ensure their readiness in facing future educational challenges.